Bonus payments and reference point violations - Axel Ockenfels; Dirk Sliwka; Peter Werner (Institute for the Study of Labor (IZA), 2010)
We investigate how bonus payments affect satisfaction and performance of managers in a large, multinational company. We find that falling behind a naturally occurring reference point for bonus comparisons reduces satisfaction and subsequent performance. The effects tend to be mitigated if information about one's relative standing towards the reference point is withheld.
Keywords: D03; M52; 330; Reference points; incentives; bonus payments; job satisfaction; job performance